Genotyping of Portuguese MTC (Mycobacterium tuberculosis complex) animal strains - Duarte, EL (2013)
During five years (2002-2007), 295 MTC animal isolates, representing 25% of the total isolations from the bovine TB national eradication programme, were genotyped by spoligotyping and MIRU-VNTR typing. Main purposes were to assess the discriminatory power of different typing techniques and their usefulness for the Portuguese epidemiological scenario, to confirm transmission hypothesis between different cattle herds, and to evaluate strain sharing between different animal species, especially between ruminants and wildlife. Isolates, previously identified by PCR-REA gyrB as M. bovis (n=283), M. caprae (n=10) and M. tuberculosis (n=2), from different animal species (cattle, n=258; goat= 8; deer, Cervus elaphus, n=21; wild boar, Sus scrofa, n=6 and mandrills, Mandrillus sphinx, n=2) were spoligotyped using 43 spacers home made membranes. A sub panel of 177 isolates, representing the most frequent spoligotypes and those shared between domestic and wildlife species, of the same geographical region, were MIRU-VNTR typed, using an 8 VNTR loci set (3232, 2164, 2461, 2996, 2163b, 2163a, 0577, 0580). SB0121 was the most frequent spoligotype (26.3%). Discriminatory power of both spoligotyping (Hunter-Gaston index, h=0.89) and MIRU-VNTR typing (h=0.97) was high, concordant with a low prevalence setting. Ten new spoligotypes were found and most had evolved through additional spacer deletions from SB0121. Four VNTR loci discriminated superiorly (3232, 2165, 2461, 2163a), and retained, together, 99% discriminating ability of the entire set. Genotyping and animal movements allowed tracing transmission routes between different herds. Still, for eight isolates, with identical genotypes, from four different herds of the same area, no cattle movements were recorded appointing for an unknown common infection source. Strain sharing between domestic and feral species was recorded in two regions, proving evidence of strains transmission between cattle and wild boar, and cattle and deer. Future goals are to use genotyping as a supportive tool for epidemiological monitoring and effective eradication measures, as well as to further evaluate if feral species could hamper bTB eradication, clarifying whether if they act as spillover or maintenance hosts.